Management of chylous ascites following pancreaticobiliary surgery. Issue 5 (24th April 2019) - Singh, Harjeet; Pandit, Narendra; Krishnamurthy, Gautham; Gupta, Rajesh; Verma, Ganga R; Singh, Rajinder
Abstract : Background: Chyle leak is an uncommon form of ascites occurring due to the accumulation of lipid‐rich lymph into the peritoneal cavity. Traumatic injury to the lymphatic system due to pancreaticobiliary surgery can lead to this phenomenon. Method: We retrospectively evaluated the data of 159 patients of pancreticobiliary surgery from January 2012 to December 2016. Five patients (5/137, 3.6%) sustained a chylous leak following pancreaticoduodenectomy and one patient (1/22, 4.5%) sustained a chylous leak following Roux‐en‐Y hepaticojejunostomy for postcholecystectomy biliary stricture. Results: Average daily output was 441 mL ( range : 150–800 mL/day), and total duration of output was 16.5 days ( range : 4–35 days). Mean hospital stay increased to 19.1 days ( range : 10–40 days). All the patients were successfully managed conservatively with a combination of customized enteral feeds, supplemental parenteral nutrition, and octreotide. One patient required additional percutaneous drainage. Conclusion: Chyle leak can be successfully treated with conservative management but at the cost of increased hospital stay. Abstract : Chyle leak is a rare complication following pancreaticobiliary surgery. There is no clear‐cut management guideline. This paper highlights the possible mechanism of chyle leak and its management.